"The Consolation of Christ": Thomas More's christening of pagan Consolatio in his Sadness of Christ. Issue 1 (June 2019) - McCarthy, John M.
Abstract : This essay places More's Sadness of Christ in the ancient genre of consolatio . Arising out of Socrates' use of philosophy as a means of consolation in the Phaedo, the genre was epitomized in Boethius' Consolation of Philosophy . In the genre, philosophy, with the help of poetry and rhetoric, provides moral remedies to suffering man with the hope of reordering his passions, intellect, and will to their true good. In other words, the genre of consolatio is philosophy's attempt to provide a solution to the moral problem of evil. Thomas More's Sadness of Christ is a Christian version of this ancient genre. While appropriating philosophical principles and images, More recasts those principles and images in the light of faith, and gives the Christian martyr's proper preparation for death and suffering by reordering his passions and intellect to their proper good through consolation in prayer and meditation on the sufferings of Christ.